A system for epigenetic concept development through autonomous associative learning - Grabowski, L.M.; Luciw, M.D.; Juyang Weng (2007 IEEE 6th International Conference on Development and Learning, 2007)
In early development, an autonomous agent must learn to understand its sensors. This is thought to be done via exploratory movements. These result in low-level understanding by exploring sensorimotor associations. This paper is concerned with the further development of internal sensors that can sense and convey a concept. A concept is an abstract and compact representation of information from multiple sources. This paper introduces a system for the development of concepts, with the key features of associative learning, internal attention pathways, and exploratory movements. It is shown, within a mobile agent in a simulation environment, to develop an internal sensor that measures the semi-concrete concept of distance traveled. Distance is shown to be understood correctly when the agent is moved, either passively or actively, in different environments and at a set of movement speeds. This system is general, and can be used to develop other concepts for other types of agents.